Skrinning Hipertensi Dan Senam Hipertensi Pada Wanita Usia Subur (Wus) dalam Pencegahan Stunting Di Desa Motui Kabupaten Konawe Utara - Hikmandayani, Hikmandayani; kartini; Hasmia Naningsih; Halijah; Farming (Poltekkes Kemenkes Kendari, 2024)
Hypertension is still a major problem in Indonesia, Non-communicable diseases that can be experienced by women such as hypertension are one of the global health problems. Hypertension is a serious health problem for women today. Providing hypertension exercise treatment that is carried out consistently is one way to maintain physical fitness that can stimulate heart activity to be able to make beneficial changes in the body of hypertension sufferers in women of childbearing age or the elderly. By doing hypertension exercise, body activity will encourage the heart to work optimally and can lower and maintain blood pressure so that it remains stable within normal limits (Sobarina, Rohimah and Ginanjar, 2022). Hypertension sufferers rarely do physical activity and exercise, this will affect the effectiveness of circulation in the blood vessel area, because fat that sticks to the blood vessels will accumulate and form plaque in the area of ??the blood vessel walls which will result in increased blood pressure (hypertension) (Moonti et al., 2022). An initial survey of mothers in Bajoe Village, Soropia District, out of 10 interviewed, all of them did not know about the dangers of hypertension in women of childbearing age. Based on the explanation above, it is considered necessary to conduct counseling on hypertension, hypertension screening and hypertension exercise for women of childbearing age (WUS) in order to increase the knowledge of women of childbearing age about hypertension, and to be able to make prevention efforts through hypertension exercise. Based on the results of the pretest and posttest, there was an increase in the knowledge of women of childbearing age about hypertension, it was known the number of women of childbearing age who experienced hypertension and an increase in the ability of women of childbearing age to do hypertension exercise